2010
DOI: 10.1167/10.10.15
|View full text |Cite
|
Sign up to set email alerts
|

The role of contrast sensitivity in global motion processing deficits in the elderly

Abstract: This study compared the effects of age on the perception of translational, radial, and rotational global motion patterns. Motion coherence thresholds were measured for judging the direction of each motion type as a function of contrast (visibility) and temporal sampling rate in young and elderly participants. Coherence thresholds decreased as dot contrast increased asymptoting at high dot contrasts but were higher in elderly compared to young participants. This equated to global motion impairment in the elderl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
63
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(76 citation statements)
references
References 43 publications
11
63
2
Order By: Relevance
“…Even in instances where there is a minimal effect of age, decreasing dot contrast has a more profoundly deleterious effect on performance levels of older participants. As mentioned previously, Allen et al (2010) have shown that when high contrast dots move at 5.6 deg/sec, older and younger adults' motion discrimination performance is comparable. However reducing dot contrast led to elevated motion coherence thresholds (impaired performance) for older, compared to younger adults.…”
Section: Global Motionsupporting
confidence: 72%
See 2 more Smart Citations
“…Even in instances where there is a minimal effect of age, decreasing dot contrast has a more profoundly deleterious effect on performance levels of older participants. As mentioned previously, Allen et al (2010) have shown that when high contrast dots move at 5.6 deg/sec, older and younger adults' motion discrimination performance is comparable. However reducing dot contrast led to elevated motion coherence thresholds (impaired performance) for older, compared to younger adults.…”
Section: Global Motionsupporting
confidence: 72%
“…Even when age-related optical factors such as lenticular yellowing and decreased pupil diameter have been accounted for, problems in spatial and temporal vision persist (e.g. Elliott, Whitaker, & MacVeigh, 1990;Whitaker & Elliott, 1992;Elliott, Choi, Doble, Hardy, Evans & Werner, 2009;Allen et al, 2010). Moreover, Ball and Sekuler (1986) assessed the effects of positive optical blur (0.00 to + 4.00 dioptres) on visual acuity and global motion discrimination in young participants.…”
Section: Optical Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the stimulus parameters used here should be above older adults' thresholds (Snowden and Kavanagh, 2006), we ruled out a relationship between measured contrast sensitivity and detection performance, which suggests that optical differences did not contribute to our results (cf. Allen et al, 2010). Older adults were overall slower to respond to targets, but we found no differential effect of task (detect/select), suggesting that this age difference reflects general age-related slowing rather than a deficit specific to the attentional task.…”
Section: Discussionmentioning
confidence: 48%
“…With regard to the weaker spatial suppression reported in older observers (Betts et al, 2005), subsequent studies have failed to replicate this effect (Karas & McKendrick, 2011) and other studies, again using stimuli designed to selectively target V5, have concluded that any motion deficits in older observers are primarily a result of contrast sensitivity loss (Allen et al, 2010). Intrigued by the counterintuitive idea that older observers were performing better than their younger counterparts, we carried out a series of experiments in which we reproduced a "suppressive" effect in younger observers very similar to that of Tadin et al, and we also showed that this effect was absent in older observers, akin to the study of Betts et al ).…”
Section: Spatial Suppressionmentioning
confidence: 99%